2000
DOI: 10.1038/sj.mp.4000664
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H2 receptor gene variants: lack of association with schizophrenia

Abstract: A role of histaminergic neuronal systems in schizophrenia was suggested by an association with several polymorphisms located in the coding region of the histamine H 2 -receptor (H2R) gene (Orange et al, Mol Psychiatry 1996; 1: 466-469). Using either the reference method of direct sequencing or restriction endonuclease digestion of PCR products amplified from DNA, we could not confirm the existence of these polymorphisms in 53 Swedish controls, 52 French controls and 88 French schizophrenics. In contrast, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
2
21
6
Order By: Relevance
“…The multiple transcription initiation sites of the human H 2 receptor gene have been mapped and an 85-bp segment (2610 to 2525 bp) immediately upstream of the initiation site was identified to exhibit a strong promoter activity in the gastric adenocarcinoma, MNK45, expressing the H 2 receptor (Murakami et al, 1999). Several H 2 receptor polymorphisms have been observed with changes, located in the gene promoter or in the coding region, including a nucleotide change leading to an Asn217Asp change (Orange et al, 1996a,b;Ito et al, 2000;Garcia-Martin et al, 2009;Micallef et al, 2013). Currently, no consensus has been obtained on a potential link of the Asn217Asp change to schizophrenia (Orange et al, 1996b;Ito et al, 2000) Currently, there is no direct structural information available for the H 2 receptor.…”
Section: A Receptor Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The multiple transcription initiation sites of the human H 2 receptor gene have been mapped and an 85-bp segment (2610 to 2525 bp) immediately upstream of the initiation site was identified to exhibit a strong promoter activity in the gastric adenocarcinoma, MNK45, expressing the H 2 receptor (Murakami et al, 1999). Several H 2 receptor polymorphisms have been observed with changes, located in the gene promoter or in the coding region, including a nucleotide change leading to an Asn217Asp change (Orange et al, 1996a,b;Ito et al, 2000;Garcia-Martin et al, 2009;Micallef et al, 2013). Currently, no consensus has been obtained on a potential link of the Asn217Asp change to schizophrenia (Orange et al, 1996b;Ito et al, 2000) Currently, there is no direct structural information available for the H 2 receptor.…”
Section: A Receptor Structurementioning
confidence: 99%
“…Several H 2 receptor polymorphisms have been observed with changes, located in the gene promoter or in the coding region, including a nucleotide change leading to an Asn217Asp change (Orange et al, 1996a,b;Ito et al, 2000;Garcia-Martin et al, 2009;Micallef et al, 2013). Currently, no consensus has been obtained on a potential link of the Asn217Asp change to schizophrenia (Orange et al, 1996b;Ito et al, 2000) Currently, there is no direct structural information available for the H 2 receptor. Yet, the H 2 receptor possesses many of the key prototypical amino acid residues common to the family A aminergic GPCRs, and homology modeling on the basis of the published H 1 receptor X-ray structure and available mutagenesis data leads to reasonable models (Fig.…”
Section: A Receptor Structurementioning
confidence: 99%
“…For each of the three promoter regions of the ECE1 gene, B1000 base pairs (bp) of genomic DNA were amplified by polymerase chain reaction (PCR) in 30 healthy individuals, using AmpliTaq Gold (Perkin-Elmer), as described previously (ECE-1a, ECE-1c), 27 or GC-RICH PCR System (Roche Diagnostics), following manufacturer's instructions (ECE-1b-ECE-1d). PCR products were screened for sequence variations by direct sequencing on a Li-Cor 4000L automated DNA sequencer, as described previously.…”
Section: Polymorphism Screeningmentioning
confidence: 99%
“…PCR products were screened for sequence variations by direct sequencing on a Li-Cor 4000L automated DNA sequencer, as described previously. 27 Wild-type and variant sequences were analyzed for cis-elements using the computer program MatInspector (http://transfac. gbf.de/TRANSFAC).…”
Section: Polymorphism Screeningmentioning
confidence: 99%
“…Studies of the sole polymorphism (543-G/A) identified within the H2 coding region suggest this variant is also not important [Ito et al, 2000;Mancama et al, 2000a], and this is clearly demonstrated upon examination of combined data from existing studies (see Fig. 1).…”
Section: Histamine Receptor Variants In Schizophreniamentioning
confidence: 80%